Analysis of digital transformation of public administration in improving the effectiveness of government services in Indonesia - Sigit Wahyudi; Aldian Yusup; Muhammad Rizki Perdana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Digital transformation has become a central pillar in reshaping public administration systems worldwide, including in Indonesia, where government institutions are increasingly adopting digital platforms to enhance service quality. Despite strong national policies such as the Electronic-Based Government System (SPBE), significant gaps remain between regulatory frameworks and practical implementation at central and local levels. This study aims to analyze how digital transformation has influenced the effectiveness of government services in Indonesia by examining implementation patterns, enabling factors, persistent barriers, and societal impacts. Using a qualitative literature review approach, the research synthesizes peer-reviewed studies, government documents, and international reports to identify trends in system integration, human resource capacity, technological infrastructure, and governance readiness. The findings reveal that digital transformation has improved service speed, transparency, and citizen experience, as demonstrated in systems such as OSS-RBA, SIPD, and Jakarta’s JAKI application. However, these benefits are uneven due to interoperability issues, inadequate digital competencies among civil servants, fragmented infrastructure, cybersecurity vulnerabilities, and regional budget disparities. Case evidence shows that successful digitalization occurs when strong policy frameworks are supported by institutional commitment, aligned regulations, robust infrastructure, and user-centered service design. Conversely, misaligned legal procedures, partial system adoption, and organizational resistance hinder effectiveness. This study concludes that Indonesia’s digital governance progress is promising yet incomplete, requiring stronger integration, capacity building, and equitable infrastructure development. The analysis contributes to a deeper understanding of how digital transformation can be strategically strengthened to support efficient, transparent, and citizen-centric public administration.